Whole-Plant Seedling Functional Traits Suggest Lianas Also Support “Fast-Slow” Plant Economics Spectrum - Zhenhua Sun (2022)
Lianas are predicted to perform better than trees during seasonal drought among tropical forests, which has substantial implications for tree and forest dynamics. Here, we use whole-plant trait comparison to test whether lianas allocated on the resource acquisitive end of the continuum of woody plant strategies. We measured morphological and biomass allocation traits for seedlings of 153 species of trees and lianas occurring in a tropical forest in Thailand during the dry season. We first compared trait differences between lianas and trees directly, and then classified all species based on their trait similarities. We found that liana seedlings had significantly higher specific leaf areas and specific stem lengths than co-occurring tree seedlings. Trait similarity classification resulted in a liana-dominated cluster and a tree-dominated cluster. Compared to the tree-dominated cluster, species in the liana-dominated cluster were characterized by a consistent pattern of lower dry matter content and cheaper and more efficient per dry mass unit investment in both above-and below-ground organs. The consistency of all organs operating in tandem for dry matter content, together with optimized investment in them per mass unit, implied that the lianas and trees can be highly overlapped on the strategy gradient of the resource acquisition continuum.